2020
DOI: 10.3389/fpubh.2020.502307
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Fitness Is Associated With Drop Out From Sport in Norwegian Adolescents. A Longitudinal Study

Abstract: Several studies indicate that participation in organized sport may result in higher physical activity levels among youth which are associated with high levels of cardiorespiratory fitness. However, no study has examined whether cardiorespiratory fitness (VO2peak) is associated with drop out from sport. The study was a 5-year longitudinal study which followed a sample of adolescents, with measures of cardiorespiratory fitness, weight and height between the age of 14 and 19 yrs. Self-reported data about particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Different physical resources and abilities also appear as grounds for dropping out of football. This finding is supported by earlier research pointing to physical resources as a reason for dropping out [ 6 , 8 , 14 , 17 ]. Lagestad [ 8 ] refer to a lower oxygen absorption level and height as reasons for dropping out of organised sport.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Different physical resources and abilities also appear as grounds for dropping out of football. This finding is supported by earlier research pointing to physical resources as a reason for dropping out [ 6 , 8 , 14 , 17 ]. Lagestad [ 8 ] refer to a lower oxygen absorption level and height as reasons for dropping out of organised sport.…”
Section: Discussionsupporting
confidence: 83%
“…Lagestad [ 8 ] refer to a lower oxygen absorption level and height as reasons for dropping out of organised sport. Other studies found that the dropout rate is higher among young people who have come less far in their physical development [ 16 , 17 , 33 , 35 ]. We will argue that this finding is related to Deci and Ryan [ 25 ] self-determination theory, pointing to the feeling of competence as a basic need in all humans, essential for optimal motivation and well-being.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this improvement in the physical fitness of adolescents is associated to an improvement in sports performance in many sport modalities such as football, alpine ski, or tennis [11][12][13]. These benefits could also lead to adolescents staying longer in sport [14].…”
Section: Introductionmentioning
confidence: 99%
“…The drop-out rates from sports gradually increase across adolescence [ 13 ]; this is associated with physical inactivity later in life, thus contributing to unhealthy lifestyles [ 14 ]. Conversely, young people who exercise keep healthy lifestyle habits, such as continued physical activity and healthy nutrition [ 15 ]. Findings in Sport and Physical Activity surveys [ 16 , 17 ] showed that the percentage of young people aged 15–24 years who exercise regularly decreased in ten years from 14% to 9%.…”
Section: Introductionmentioning
confidence: 99%